2019
DOI: 10.5765/jkacap.190027
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Artificial Intelligence in Screening and Diagnosis of Autism Spectrum Disorder: A Literature Review

Abstract: Objectives:The detection of autism spectrum disorder (ASD) is based on behavioral observations. To build a more objective datadriven method for screening and diagnosing ASD, many studies have attempted to incorporate artificial intelligence (AI) technologies. Therefore, the purpose of this literature review is to summarize the studies that used AI in the assessment process and examine whether other behavioral data could potentially be used to distinguish ASD characteristics. Methods: Based on our search and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 52 publications
(81 reference statements)
0
22
0
1
Order By: Relevance
“…Furthermore, it articulated the content mentioned above and provided a forward path that recommends using machine learning in ASD to win regard to implementation, conceptualization, and mining data. Besides, Song et al [96] dispensed a comprehensive survey on the use of artificial intelligence in screening ASD. It briefly reviewed existing ASD assessment techniques, facial expression, motor movement data analysis, and their results on different learning algorithms.…”
Section: Related Surveysmentioning
confidence: 99%
“…Furthermore, it articulated the content mentioned above and provided a forward path that recommends using machine learning in ASD to win regard to implementation, conceptualization, and mining data. Besides, Song et al [96] dispensed a comprehensive survey on the use of artificial intelligence in screening ASD. It briefly reviewed existing ASD assessment techniques, facial expression, motor movement data analysis, and their results on different learning algorithms.…”
Section: Related Surveysmentioning
confidence: 99%
“…Based on the reviewed literature, we sought the answer on whether the recent findings could sufficiently translate to real-life implementation of ML-based ASD screening and diagnostic models. Nonetheless, previous literature reviews assessed the performance of ML models in ASD screening and diagnosis based on the common evaluation metrics of sensitivity, specificity, and accuracy, among others [ 25 , 28 ]. However, none of the existing literature reviews systematically analyzed the subject area and provided enough evidence on the readiness and sufficiency of the models toward real-life implementation of the ML-based systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, none of the existing literature reviews systematically analyzed the subject area and provided enough evidence on the readiness and sufficiency of the models toward real-life implementation of the ML-based systems. For instance, Song et al [ 28 ] reviewed 13 relevant studies that utilized varying data types and discussed the possibility of achieving effective classification of ASD based on the study findings. Similarly, Thabtah [ 25 ] identified some limitations within the commonly employed research methodologies and proposed intuitive stages toward appending the ML models into ASD screening apps.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome administrator bias during assessments, many have attempted to use AI technology to create a more concise algorithm for ASD diagnosis. 7 Several studies have attempted to classify items from assessment of ASD diagnostic instruments that are most predictive of the diagnosis to make the process less time-consuming. Wall et al 8 applied 16 ML algorithms with data in multiple ASD data repositories, including the Autism Genetic Resource Exchange (AGRE) and Autism Consortium (AC), and they suggested that ML enables the classification of autism and non-autism with 100% accuracy using tree algorithms such as ADTree.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome administrator bias during assessments, many have attempted to use AI technology to create a more concise algorithm for ASD diagnosis [ 7 ]. Several studies have attempted to classify items from assessment of ASD diagnostic instruments that are most predictive of the diagnosis to make the process less time-consuming.…”
Section: Introductionmentioning
confidence: 99%